Effectiveness and Safety of LMWH Treatment in Patients With Cancer Diagnosed With Non-High-Risk Venous Thromboembolism: Turkish Observational Study (TREBECA). (September 2018) - Ozaslan, Ersin; Ozkan, Metin; Cicin, Irfan; Benekli, Mustafa; Kocer, Murat; Uysal, Mukremin; Oksuzoglu, Berna; Isikdogan, Abdurrahman; Cubukcu, Erdem; Elkiran, Emin T.; Dane, Faysal; Aliustaoglu, Mehmet; et al.
We compared the efficacy and safety of low-molecular-weight heparins (LMWHs) in patients with cancer who are at low risk of venous thromboembolism (VTE). Patients were treated by medical oncologists in Turkey at 15 sites, where they were enrolled and followed up for a period of 12 months. Due to the study design, there was no specific treatment protocol for LMWH. Primary end points were efficacy and the time to change in VTE status. Of the included 250 patients, 239 (95.6%), 176 (70.4%), 130 (52.0%), and 91 (36.4%) completed their day 15, month 3, month 6, and month 12 visits, respectively. Number of patients treated with enoxaparin, bemiparin, and tinzaparin were 133, 112, and 5, respectively. Anticoagulant therapy provoked thrombus resolution in 1.2% and 12.7% of patients using enoxaparin and bemiparin, respectively ( P = .004). Thrombus resolution was observed in 81 more patients at month 3 visit. This ratio was 35 (40.2%) of 87 and 46 (54.1%) of 85 patients administered enoxaparin and bemiparin at the third visit, respectively ( P = .038). Thrombus resolution was observed in 21 more patients during month 6 visit. This ratio was 5 (7.7%) of 65 and 15 (23.4%) of 64 patients administered enoxaparin and bemiparin at the fourth visit, respectively ( P = .022). The LMWH was discontinued in only 2 patients due to gastrointestinal bleeding. This pioneering study shows bemiparin is more effective than enoxaparin in thrombosis resolution and has a similar tolerability profile.